Adiabatic operation slope-loss algorithm for ultrashort and broadband waveguide taper - Liang, Tu-Lu; Cheng, Xi; Yu, Mei; Zhang, Lingyan; Shi, Jin; Shao, Wei (Frontiers in Physics, 2022)
In this paper, an adiabatic operation slope-loss algorithm (AO-SLA) is developed for designing efficient adiabatic waveguide tapers. The algorithm can compute the efficient adiabatic guided-wave shape of the waveguide taper. A well-studied case of an adiabatic waveguide taper is used to show how it can readily generate a guided-wave shape that gives the same mode-connection power transfer with a much shorter length compared with the linear shape. In the waveguide taper design, it is shown that the device efficiency designed with AO-SLA is better than that based on the parabolic case and the SLA case, and the adiabatic taper designed can give a broad operating bandwidth. Moreover, the adiabatic condition α for AO-SLA can be very large.